2010
DOI: 10.1111/j.1365-2230.2010.03790.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic variant of hypereosinophilic syndrome

Abstract: Hypereosinophilia may be associated with any of several underlying diseases. Atopy or allergic drug reactions are the most common causes, but infections with bacteria and parasites should also be considered in the differential diagnosis. When thorough evaluation of a patient with chronic hypereosinophilia fails to reveal an underlying disease, the diagnosis of idiopathic hypereosinophilic syndrome (HES) should be considered. We report a patient with unexplained persistent hypereosinophilia associated with a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(36 reference statements)
0
4
0
1
Order By: Relevance
“…There are also reports of the formation of venous thrombi, which are potentially fatal. 4 Our patient had a massive pulmonary embolic event after 1 year of a normal blood eosinophil count but preceded by Cardiac magnetic resonance showed no sign of cardiac infiltration, although the gold standard is still the biopsy, which was not performed. Kim et al 12 reported a massive thromboembolism attributable to a left ventricular thrombus associated with HES, with no definite finding of eosinophil infiltration in the pathologic evaluation of the removed thrombus.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…There are also reports of the formation of venous thrombi, which are potentially fatal. 4 Our patient had a massive pulmonary embolic event after 1 year of a normal blood eosinophil count but preceded by Cardiac magnetic resonance showed no sign of cardiac infiltration, although the gold standard is still the biopsy, which was not performed. Kim et al 12 reported a massive thromboembolism attributable to a left ventricular thrombus associated with HES, with no definite finding of eosinophil infiltration in the pathologic evaluation of the removed thrombus.…”
Section: Discussionmentioning
confidence: 74%
“…This lymphocytic variant is associated with elevated interleukin-5 and immunoglobulin E in the absence of atopy. 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our clinical case demonstrated a dual presentation: conventional CTLA-4h manifestations combined with an unusually severe reactive hypereosinophilic syndrome (L-HES). This syndrome involves dysregulated “T cell” production of IL-4, IL-5, and/or IL-13, with IL-5 as the principal driver of eosinophilic overproduction ( 34 36 ). Notably, we found that DECTIN-1 signaling suppressed γδ T cell–derived IL-5, implying that partial loss of DECTIN-1 in the patient could contribute to hypereosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…T 淋巴细胞分泌的嗜酸性细胞因子增加 [2][3][4] ,后者最常见的基 因异常是 FIP1L1-PDGFRA 融合基因,4 号染色体上的间隙 缺失导致干细胞突变 [5] ,它显示结构性酪氨酸激酶活性,并 被认为导致嗜酸性粒细胞过度生产。 这些亚型均与临床表现、 预后和治疗反应的差异有关 [5] [6] 。 然而,环境污染、相关感染及食品问题是否会导致 HED 的发生, 还需要更多研究来支持 [7] [9] 。在继发性 HES 中,嗜酸性粒细 胞本身不是克隆性的,但它们在靶组织中的扩张和激活与克 隆性 T 细胞、淋巴瘤或其他实体肿瘤等有关,这些因素会导 致嗜酸性粒细胞的扩张和嗜酸性粒细胞相关的器官损伤。大 多数 HES 病例将被归类为特发性 [10][11][12] 。据估计,10~15% 的 HES 患者可能属于 L-HES 表型,但由于无法检测到某些异 常的免疫表型,这一数字可能被低估了 [13] 。 家族型 HES 是一种罕见的疾病,其病因不明的显著嗜酸 性粒细胞增多症在后代中出现。通常表现为是无明显症状, 但一些受影响的家庭成员出现类似于 F/P 阳性 HES 的临床表 现,并可能伴有心脏纤维化和神经异常 [14] 。 内部及外部多种因素可以共同影响到 HED,对于 HED 目前还没有确切的分类方法。但是我们可以借鉴上文介绍的 HES 的分类方法,也可以把 HED 分为特发性 HED、原发性 HED、继发性 HED [15] [16] 。糖皮质激素可以作为所有类型 HES 的 一线稳定疗法,尽管最近的研究表明,糖皮质激素的临床反 应在很大程度上取决于 HES 亚型,髓系和淋巴细胞变异体的 反应最差 [17] 。这一结果也可反映出不同 HED 患者对糖皮质 激素的敏感性也不尽相同。 泼尼松的推荐起始剂量是每天 0.5~1mg/kg,但如果嗜酸 性粒细胞增多和症状不严重,可以先尝试较低的剂量 [18] [18] 。 还有一些研究表明, 这是一种有效的联合用药。 羟基脲在很多患者中因无效或不良反应而停用 [10] 。一般来说, 羟基脲不应作为单一治疗方案,当与皮质类固醇或干扰素 -α 联合使用时可能最有效 [18] 。…”
Section: Hes(l-hes)和骨髓增殖型 Hes(m-hes),前者是由于unclassified